2016
DOI: 10.1186/s13662-015-0720-3
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of rhizosphere microbial degradation with impulsive diffusion on nutrient

Abstract: In this paper, a new mathematical modeling of rhizosphere microbial degradation with impulsive diffusion is proposed. By using the Floquet theorem, we find the rhizosphere microbe-eradication periodic solution is globally asymptotically stable if some conditions are satisfied. At the same time we also obtain the permanent conditions of the nutrients and rhizosphere microbe. Finally, a system of equations is solved by using a numerical simulation to justify our results. MSC: 34C05; 92D25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Further, the microbial parameterization of these models are largely based on limited bacterial datasets, typically generated ex situ, and ignore the presence of key components of the rhizosphere (e.g. fungi, mycorrhizas, mesofauna; Raynaud, 2010;Zhao et al, 2016). Further, they make gross assumptions on the spatial and temporal dynamics of exudate release in soil.…”
Section: Modellingmentioning
confidence: 99%
“…Further, the microbial parameterization of these models are largely based on limited bacterial datasets, typically generated ex situ, and ignore the presence of key components of the rhizosphere (e.g. fungi, mycorrhizas, mesofauna; Raynaud, 2010;Zhao et al, 2016). Further, they make gross assumptions on the spatial and temporal dynamics of exudate release in soil.…”
Section: Modellingmentioning
confidence: 99%
“…In their work, the numerical results demonstrated that the virus-free equilibrium is globally stable. In addition, several applications of the impulsive models have been studied in, e.g., [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%